Heat transfer performance of Tio2– SiO2 nanofluid in water-ethylene glycol mixture - Muhammad Nabil Fikri, Mohamad; Azmi, W. H.; Khamisah, Abdu Hamid; R., Mamat (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malaysia., 2018)
In recent years, there has been an increasing interest in combination of two or more nanoparticles due to the improvement in force convection heat transfer of fluids. Through recent studies, combination of two different nanoparticles suspended in base fluid and known as hybrid nanofluids have a better performance of heat transfer. This paper presents the heat transfer performance of the combination of Titanium oxide (TiO2) and Silicon oxide (SiO2) nanoparticles dispersed in 60:40 volume ratio of water and ethylene glycol mixture as a base fluid. The hybrid nanofluids were prepared using two-step method and homogenized to firm the suspension for three different volume concentration of 0.5%, 1.0% and 1.5%. The forced convection heat transfer experiment was conducted at working temperature 70 °C with a constant heat flux condition. The Nusselt number and heat transfer coefficient of hybrid nanofluids was compared with the base fluid. It shows that, the increment in nanofluids concentration affect an increasing of Nusselt number and heat transfer coefficient. The enhancement of convective heat transfer is 22.9% and 15.1% for volume concentration of 1.0% and 0.5%, respectively. The highest enhancement of convective heat transfer is found at 1.5% volume concentration by 30.8%.